Effects on Quality Properties of Pork Sausages Enriched with Sea Buckthorn (Hippophae rhamnoides L.). (1st August 2017) - Salejda, Anna Marietta; Nawirska-Olszańska, Agnieszka; Janiewicz, Urszula; Krasnowska, Grażyna
Abstract : The present study was aimed at evaluating the effect of a sea buckthorn ( Hippophae rhamnoides L.) fruit extract on selected quality properties of cooked sausages. The ethanolic extract of sea buckthorn fruit (SBE) incorporated at the highest level (3%) significantly affected the pH, weight losses, and instrumental color parameters of sausages. The SBE deteriorated organoleptic properties of sausages like juiciness, overall appearance, texture, and taste; however the sausages manufactured with 1.5% SBE were scored higher for color and almost the same as control for smell acceptance. Textural parameters like hardness, springiness, gumminess, and chewiness of cooked sausages decreased along with SBE addition. After 28 days of storage, the samples with 1.5% SBE addition were as springy, hard, and gummy as the control ones. Incorporation of SBE increased the shelf life of sausages. The highest inhibition of lipid oxidation was observed in the samples manufactured with 1.5% SBE. The SBE significantly improved the microbial qualities of sausages.